Assessing EU concessions for service trade liberalization in the Doha Round: What frequency indices suggest - Rolf J. Langhammer (Kiel Institute for World Economics (IfW), 2003)
While the EU is a customs union in merchandise trade (goods), it has not yet reached this stage of integration in service trade. How far the EU is from a customs union in service trade is very difficult to assess because of the nonquantitative nature of trade restrictions in this sector. The paper tries to present first indirections of how far the EU is from being a customs union by calculating frequency indices of trade measures using the Hoekman approach based on the February 2003 EU first offer regarding service trade in the Doha Round. The calculations show that differences in national policies against nonmember states are particulary relevant in modes of supply via factor movements. Inter alia, policy measures comprise national needs tests, residence criteria, and nationality criteria. The paper concludes that there is reason to assume that in the course of the Doha Round negotiations some if not many of national measures will be given up. Therefore multilateral trade negotiations will be instrumental to bring the EU to a complete customs union as it happened in goods trade between 1958 and 1968 when the Dillon Round and the Kennedy Round helped to complete the customs union in industrial goods.
Keywords: F1; F2; 330; Services; EU policy; Doha Round; Trade liberalization; Internationaler Dienstleistungsverkehr; Außenhandelsliberalisierung; Nichttarifäre Handelshemmnisse; Außenhandelspolitik; EU-Staaten